Pulmonary and sinus diseases in primary humoral immunodeficiencies with chronic productive cough. Issue 12 (11th December 2003) - Rusconi, F; Panisi, C; Dellepiane, R M; Cardinale, F; Chini, L; Martire, B; Bonelli, N; Felisati, G; Pietrogrande, M C
Abstract : Aims: To prospectively evaluate sinopulmonary disease in 24 patients with primary humoral immunodeficiency (11 with agammaglobulinaemia, nine with isolated IgA deficiency, and two with common variable immunodeficiency) and chronic productive cough, ascertain the usefulness of chest high resolution computed tomography (HRCT) in evaluating the progression of lung disease, and test a therapeutic approach to chronic sinusitis. Methods: Pulmonary abnormalities were evaluated using lung function tests and HRCT (Bhalla score); chronic sinusitis was diagnosed clinically and confirmed by flexible fibreoptic endoscopy. Sixteen patients entered the three year follow up. Results: Lung function testing revealed an obstruction in four patients; chest HRCT was abnormal in 16. There was a linear relation between the Bhalla score ⩾4 and the number of months with cough/year over the previous two years (clinical score), and between the difference in clinical scores during follow up and in the previous two years and the difference in Bhalla score. The pulmonary lesions did not significantly progress over a three year period. Thirteen patients had chronic sinusitis; 6/10 patients followed up were successfully treated with antibiotics plus topical therapy and two with nasal polypoid disease with endoscopic sinus surgery. Conclusions: In patients with primary humoral immunodeficiency and chronic productive cough, HRCT is very useful in delineating the extent of lung damage. The correlation between Bhalla score and clinical findings and the favourable outcome of the disease suggests that in most patients chest HRCT should not be repeated annually as previously suggested. Medical therapy seems to be effective in many cases of chronic sinusitis.